Концепт ВІРА як ціннісний постулат ідіостилю В. С. Бойка - Черненко, Ольга Ігорівна (Одеський національний університет імені І. І. Мечникова, 2021)
Статтю присвячено вивченню концепту ВІРА в мовосвіті В. С. Бойка як відомого майстра поетичного слова. Проаналізовано структуру концепту. Виокремлено ядрову, приядрову та периферійну зони. Описано художньо-семантичні наповнення мікроконцептів. Визначено авторську позицію щодо існування особистості у світі, а також індивідуально-авторські потрактування концепту ВІРА у мовомисленні митця.

The article is devoted to the study of the concept of FAITH in the idiostyle of V. S. Boyko, as a famous master of the poetic word. The structure of the concept is analyzed. The nuclear, near-nuclear and peripheral zones are highlighted. The artistic and semantic content of micro- concepts is described. The author's position on the existence of a person in the world, as well as individual author's interpretations of the concept of FAITH in the idiostyle of the artist of the poetic word are determined. Whatever paths humanity has taken, this path has always been accompanied by faith. No matter what historical epoch we are talking about, no matter what country we talk about, it is difficult to disagree with the fact that faith has greatly influenced and is influencing the lives of millions of people. And it is not only about faith in higher powers, but also faith in a happy future, faith in yourself, in your people, in the triumph of moral values and the victory of good over evil. Faith is an important spiritual existential value that encourages a person to move on. Accordingly, the study of the linguistic expression of the concept of FAITH will allow to penetrate deeper into the peculiarities of individual language thinking, to determine the author's priority guidelines. Linguistic expression of the concept of FAITH in the poetic linguistics of V. S. Boyko finds in the words faith, to believe, prayer, icon, angel, orthodox, catholic, pagan, saint, temple, church, resurrection, apostle, paradise, cross, mantis, as well as in names of Оrthodox holidays and biblical names, because for the poet is close to the Christian, Orthodox worldview. The poetic picture of the artist's world is broader than dictionary interpretations, so the concept of FAITH acquires a broader artistic and semantic content.
Concept FAITH as a value postulate of idiostyle V. S. Boyko
Keywords: концепт; художньо-семантичне наповнення; мовомислення; особистість; мікроконцепт; concept; artistic and semantic content; idiostyle; personality; microconcept